Minimally Invasive Biopsies of Deep-Seated Brain Lesions Using Tubular Retractors Under Exoscopic Visualization - Jackson, Christina; Gallia, Gary L.; Chaichana, Kaisorn L. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background and Study Aims/Objective Brain lesions in deep-seated locations can present a surgical challenge. Tissue remains the gold standard for diagnosing these lesions to guide potential adjuvant therapy. These lesions have been traditionally approached by stereotactic needle biopsy, open biopsies through craniotomies, and excisional biopsies. We provide a safe alternative method using tubular retractors under exoscopic visualization for biopsies of deep-seated brain lesions.Material and Methods All patients who underwent a biopsy with the use of a tubular retractor under exoscopic visualization of a deep-seated lesion from January 2013 to September 2016 were identified prospectively and followed. This was done for patients with lesions where extensive resection was not deemed possible because of eloquent location and/or lack of impact on the natural history of the disease.Results A total of 11 patients, with an average age (plus or minus standard deviation) of 48.7 ± 18.3 years, underwent biopsies with tubular retractors and exoscopic visualization. The locations included thalamus (n = 3), optic pathway (n = 2), deep cerebellar nuclei (n = 1), centrum semiovale/corpus callosum (n = 4), and multifocal (n = 2). Diagnosis was obtained in all patients: glioblastoma multiforme (n = 3), anaplastic astrocytoma (n = 3), demyelinating disease (n = 2), renal cell cancer (n = 1), and lymphoma (n = 2). In all cases with tumors, the molecular analyses were conducted successfully. On postoperative computed tomography, no patients had notable hematomas and no patients had new deficits.Conclusion Diagnosing brain lesions is critical for guiding potential adjuvant therapies. When surgical resection is not possible or required, we report the efficacy of a tubular retractor system with exoscopic visualization for the safe access of deep-seated lesions to provide adequate tissue for diagnosis and molecular evaluation.
Keywords: biopsy; brain tumor; deep seated; eloquent; tubular retractor